1991
DOI: 10.1177/000348949110001003
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Synkinesis following Reinnervation in the Rat: Neuroanatomic and Physiologic Study Using Retrograde Fluorescent Tracers and Electromyography

Abstract: The functional organization of laryngeal motoneurons in the nucleus ambiguous (NA) was evaluated in adult male rats before and after recurrent laryngeal nerve section and reinnervation. Using retrograde double labeling techniques with fluorescent probes, we obtained the number and position of labeled neurons by using the Bioquant 3-D imaging system. Reinnervation was documented by electromyography. In nine control animals vector analysis revealed significant (p less than .05) separation of the posterior cricoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
103
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 28 publications
10
103
0
Order By: Relevance
“…The failure of reinnervation procedures is the result of multiple factors, including decreased motor fiber density, existing laryngeal muscle atrophy, central motoneuron loss in the nucleus ambiguus, and inappropriate or misdirected innervation by antagonistic motoneurons. 7,8 The discovery of neurotrophic factors that support neuronal survival during development and neuronal function throughout adulthood has generated broad interest in the use of these factors in facilitating recovery after peripheral nerve injury. A multitude of neurotrophic factors have been shown to prevent motoneuron loss, enhance nerve sprouting, preserve motor endplate morphology, and promote reinnervation.…”
Section: Introductionmentioning
confidence: 99%
“…The failure of reinnervation procedures is the result of multiple factors, including decreased motor fiber density, existing laryngeal muscle atrophy, central motoneuron loss in the nucleus ambiguus, and inappropriate or misdirected innervation by antagonistic motoneurons. 7,8 The discovery of neurotrophic factors that support neuronal survival during development and neuronal function throughout adulthood has generated broad interest in the use of these factors in facilitating recovery after peripheral nerve injury. A multitude of neurotrophic factors have been shown to prevent motoneuron loss, enhance nerve sprouting, preserve motor endplate morphology, and promote reinnervation.…”
Section: Introductionmentioning
confidence: 99%
“…Rhee et al 40 studied laryngeal reinnervation in rats and found that it followed a random pattern. Flint et al, 41 studying key aspects of laryngeal reinnervation, also found random motoneuron organization after reinnervation. These findings suggest that adductor muscles may be innervated by abductor fibers and vice versa, resulting in reinnervation without functional recovery (laryngeal synkinesis).…”
Section: Discussionmentioning
confidence: 98%
“…An equivalent incidence of synkinetic reinnervation is believed to occur in humans. [11][12][13][14] Based on the above research assumption, we found a synkinesis incidence of 60 per cent. Although comparable to previous reports, this incidence is lower than expected.…”
Section: Discussionmentioning
confidence: 99%